Effect of Physical and Chemical Structure of Shengli Lignite on Its Spontaneous Combustion Tendency - Lin GAO; Qiong MO; Junjie LIAO; Liping CHANG; Weiren BAO (Taiyuan Ligong Daxue xuebao, 2021)
A series of oxidized coal samples were prepared by oxidation of Shengli lignite in air at 140 ℃ and 160 ℃ for different time. The functional groups and pore structure parameters of coal samples were analyzed and tested by Fourier transform infrared spectroscopy and nitrogen adsorption method. The critical ignition temperature of the oxidized coal samples was measured by the basket heat method. The spontaneous combustion kinetic parameters were calculated, and the influence of lignite physical and chemical structure on the critical spontaneous combustion temperature was discussed. The active groups in lignite play a leading role in the process of oxidative spontaneous combustion. The higher the content of alkyl side chain groups and oxygen-containing functional groups, the greater the tendency of spontaneous combustion. The pore structure of coal samples is also a factor that affects the tendency of spontaneous combustion. The larger the specific surface area and pore volume, the more active sites expose, and the more likely spontaneous combustion occurs.